Solidification of niobium-silicide-based alloys during laser additive manufacturing process. (May 2019) - Allen, A.; Douglas, A. C.; Feitosa, L. M.; Qian, H.; Li, J.; Dong, H. B.; Lin, X.; Li, Y.
Abstract: Niobium silicide-based composites, in the application of gas turbine blades, promise significant efficiency improvements compared to current Ni-based alloys. The higher temperature capability would allow the engine to run at a higher temperature than that of current alloys, increasing engine efficiency. Nb-Si based composites possess a lower density, due to the presence of ceramic phases such as Nb5 Si3 and/or Nb3 Si. This would reduce the weight of the rotating blades. However, improvements in certain properties, such as room temperature toughness and oxidation resistance are needed. This study focuses on the manufacturability aspect of the powder feeding laser additive manufacturing (LAM) process to engineering Nb-Si based alloy samples. LAM has the advantage of forming near-net shapes without the use of expensive cores and moulds for the reactive Nb-Si melt. Fine microstructure and even chemical composition distribution with reduced macro-segregation are obtained. With the use of power feeding system, new Nb-Si based alloys are LAMed with varying atomic composition. Microstructures of the LAMed alloys will be presented, and the relationship between the microstructure and the alloy chemistry will be reported.